Caste Issue in Literature and Regional Literature - Singh, Ravindra Kumar (Stallion Journal for Multidisciplinary Associated Research Studies, 2023)
The key objective of this piece of writing is to examine the manner in which caste is portrayed as a subject for two popular schools of writing in India, that is, Indian Literature in English & Indian Literature in other languages. The collaboration of David Davidar & Omprakash Valmiki is chosen for the post. Among their plays, The House of Blue Mangoes (2002) & Joothan: A Dalit's Life (2003) are selected because they deal with caste problems. Both plays are critical portrayals of the lives of low-caste citizens & their efforts to come to grips with the truth of their shackled life. This is not a question of classifying the two schools of writing, but of examining their disparities in the way they explain the caste concept as portrayed in mainstream writing and regional writing. In order to understand the developments in writing & regional writing, it is important to have an overview of Indian literature in English & Indian literature in English translation.